Some sequence spaces and statistical convergence - E. Savaş (International Journal of Mathematics and Mathematical Sciences)
We introduce the strongly (V,λ)-convergent sequences and give the relation between strongly (V,λ)-convergence and strongly (V,λ)-convergence with respect to a modulus.